Two-channel method for measuring losses in a ring optical resonator at a wavelength of. (July 2016) - Azarova, V.V.; Bessonov, A.S.; Bondarev, A.L.; Makeev, A.P.; Petrukhin, E.A.
Abstract: A two-channel method is proposed for measuring losses in an optical ring resonator (RR), in which eigenmodes (counterpropagating waves) are excited by means of a Zeeman ring He – Ne laser with a wavelength of . The measured frequency splitting of the laser counterpropgating waves is used to determine the absolute value of losses in an exemplary RR. The value of losses in the measured RR is determined by comparing the resonance width of the output radiation intensity with the resonance width of the radiation intensity for an exemplary resonator. The algorithm of intensity resonance processing takes into account the distortions caused by the dynamic effect, which allows a significant increase in the accuracy (up to 1 % – 2 %) and sensitivity of the proposed method. The measured losses in the RR with a perimeter of 28 cm constitute .